(untitled) (Research, Society and Development, 2020)
The assessment of the work context of large populations can provide a diagnosis of strategic value for organizations. In this context, this study proposes a revisiting of the work context assessment scale (EACT) of Psychodynamics of Work, according to the model proposed by Mendes (2007). As a justification for the study, it was found that (i) the need to proceed with the Confirmatory Factor Analysis (AFC) of the instrument; (ii) transformation of the variables in the positive direction, as well as (iii) inclusion of a new variable in the scale. Methodologically, 202 responses were received through the Google Forms platform, which were transported to the SPSS software, version 23. In turn, the AMOS software, version 20, was used in the operationalization of the AFC. The methodological procedures followed the models proposed by Costa (2011) for validation and measurement of scales. The results demonstrated a reduction in the number of items, as well as an increase in the level of reliability in all factors that make up the scale. Finally, it is suggested the inclusion of questions for the characterization of the sample, as well as the application of the instrument in different contexts to attest its adaptability.